Development of pink guava seed oil-palm stearine blend as lard substitute - Abd Rahman, Noor Raihana (2016)
Guava (Psidium guajava L.) belonging to the family Myrtaceae is grown widely in the tropical regions of Asia, Africa, and America. In Malaysia, pink guava fruits are used mainly for production of juices meant for export market. After production of juice, guava seeds are discarded without any productive use. The possibility of using guava seed for oil recovery, however, still remains unexplored in Malaysia. Therefore, the aim of this study was to extract and characterise pink guava seed oil and use it in combination with palm stearin to formulate lard alternative fat substitutes to be applied in products. Hence, the blends can be permissible to be used as a replacement for lard by Muslims, Jews and vegetarians. In this study, oils of pink and white guava seeds were extracted and analysed. The oil recoveries of pink guava (PGO) and white guava (WGO) seeds were 8.44% and 6.85%, respectively. The color of WGO was light yellow while that of PGO was dark yellow. The iodine value for PGO and WGO were 123.78 and 125.73, respectively. The blends were prepared by mixing pink guava seed oil with palm stearin (PGO/PS) in different ratios: PGO-1, 40:60; PGO-2, 45:55; PGO-3, 50:50; PGO-4; 55:45. The blends and lard were compared in terms of their basic physicochemical parameters, fatty acid and triacylglycerol (TAG) compositions, melting, solidification and polymorphic properties. The slip melting points (SMP) of the fat blends were found to range from 43.63 to 50.30oC. Among the four blends, PGO-1 and PGO-2 showed better compatibility to lard at most temperature. According to x-ray diffraction analysis, the diffractogram of all blends display beta and beta prime polymorphic forms which is the same as lard. The potential of the modified blends to be as lard alternative were proposed in the range of 40% to 55% with the addition of PGO. Then, the four blends were applied in the cookies as shortening to compare their performance with lard in the end products. The rheology for PGO-2 and lard looked closer to each other based on tan δ value which were 0.54 (PGO-2) and 0.53 (lard). For the test hardness, PGO-2 gave the nearest value to the lard which was 13.43N and 14.48N respectively. Thickness and width were taken to measure the dimension of cookies where PGO-2 had almost the same value with 13.68mm (PGO-2) and 13.94mm (lard) for the thickness and 66.37mm (PGO-2) and 66.54mm (lard) for the width. Appearance were tested by observing the surface island on the top of cookies where PGO-1 and PGO-2 showed less cracking which were similar to lard surface. Among the four cookies, PGO-2 showed the similarities to lard at most test. Therefore, blend of PGO-2 could be a potential blend to lard substitute.